Exploring the optimal impact force for chronic skeletal muscle injury induced by drop-mass technique in rats - Ge, Haiya; Wang, Zhengming; Yang, Zongrui; Shi, Jinyu; Lu, Jiehang; Wang, Yuanyuan; Li, Zhengyan; Du, Guoqing; Shen, Zhibi; Zhan, Hongsheng (Frontiers in Physiology, 2023)
Introduction: Skeletal muscle injuries are widespread in sports, traffic accidents and natural disasters and some of them with poor prognoses can lead to chronic skeletal muscle damage in the clinic. We induced a chronic skeletal muscle injury by controlling time and contusion force using an acute blunt trauma model that will help us better comprehend the pathological features of chronic skeletal muscle injury. Methods: Several levels of injury were induced by repeatedly striking in 5, 10, and 15 times the gastrocnemius muscle from the same height with 200g weights. After injury, the markers of muscle injury were assessed at 2 and 4 weeks by serum elisa. Electron microscopy, histologic and 2 immunohistochemical staining, and mRNA analysis were used to evaluate the ultrastructure, inflammation, extracellular matrix decomposition, and anabolism of injured muscle in 2 and 4 weeks.Results: All three different kinetic energies can result in skeletal muscle injuries. However, the injured skeletal muscles of rats in each group could not recover within 2 weeks. After 4 weeks, tissue self-repair and reconstruction caused the damage induced by 5J kinetic energy to almost return to normal. In contrast, damage induced by 10J kinetic energy displayed slight improvement compared to that at 2 weeks. Despite this, collagen fibers on the surface of the tissue were disorganized, directionally ambiguous, and intertwined with each other. Myofilaments within the tissue were also arranged disorderly, with blurry and broken Z-lines. Damage caused by 15J kinetic energy was the most severe and displayed no improvements at 4 weeks compared to 2 weeks. At 4 weeks, IL-1β, IL-6, Collagen I, and Collagen III, MMP2 expressions in the 10J group were lower than those at 2 weeks, showing a tendency towards injury stabilization. Conclusion: After 4 weeks of remodeling and repair, the acute skeletal muscle injury model induced by 10J kinetic energy can stabilize pathological manifestations, inflammatory expression, and extracellular matrix synthesis and catabolism, making it an appropriate model for studying chronic skeletal muscle injuries caused by acute injury.